Kedisiplinan Siswa SMP Negeri 1 Jempang yang Tinggal di Asrama Santo Yosef Freinadementz dan di Luar Asrama - Natalius Aling; Nikolaus Anggal (Gaudium Vestrum - Jurnal Kateketik Pastoral, 2021)
This study aims to see how the level of discipline of SMP Negeri 1 Jempang students who live in the female student dormitory of St. Yosef Freinadementz and those who do not live in the dormitory whether there are similarities or differences in the discipline. This study uses a descriptive comparative approach. Observations and in-depth interviews were used to determine student discipline. The data collected were analyzed through the stages of data reduction, data presentation, and concluding. The results of this study indicate that the average score of students living in dormitories is 74.86 with a total score of 374.3. Meanwhile, students who live outside the dormitory get an average score of 75.2 with a total score of 378.6. This value shows that students who live outside the dormitory have slightly better discipline than students who live in the dormitory. It is known that the factors that influence the discipline of students who live in dormitories are family factors, the surrounding environment, and peers.